Clinical Course of Acute Ischemic Stroke Due to Medium Vessel Occlusion With and Without Intravenous Alteplase Treatment. Issue 11 (November 2020) - Ospel, Johanna M.; Menon, Bijoy K.; Demchuk, Andrew M.; Almekhlafi, Mohammed A.; Kashani, Nima; Mayank, Arnuv; Fainardi, Enrico; Rubiera, Marta; Khaw, Alexander; Shankar, Jai J.; Dowlatshahi, Dar; Puig, Josep; et al.
Abstract : Background and Purpose: Available data on the clinical course of patients with acute ischemic stroke due to medium vessel occlusion (MeVO) are mostly limited to those with M2 segment occlusions. Outcomes are generally better compared with more proximal occlusions, but many patients will still suffer from severe morbidity. We aimed to determine the clinical course of acute ischemic stroke due to MeVO with and without intravenous alteplase treatment. Methods: Patients with MeVO (M2/M3/A2/A3/P2/P3 occlusion) from the INTERRSeCT (The Identifying New Approaches to Optimize Thrombus Characterization for Predicting Early Recanalization and Reperfusion With IV Alteplase and Other Treatments Using Serial CT Angiography) and PRoveIT (Precise and Rapid Assessment of Collaterals Using Multi-Phase CTA in the Triage of Patients With Acute Ischemic Stroke for IA Therapy) studies were included. Baseline characteristics and clinical outcomes were summarized using descriptive statistics. The primary outcome was a modified Rankin Scale score of 0 to 1 at 90 days, describing excellent functional outcome. Secondary outcomes were the common odds ratio for a 1-point shift across the modified Rankin Scale and functional independence, defined as modified Rankin Scale score of 0 to 2. We compared outcomes between patients with versus without intravenous alteplase treatment and between patients who did and did not show recanalization on follow-up computed tomography angiography. Logistic regression was used to provide adjusted effect-size estimates. Results: Among 258 patients with MeVO, the median baseline National Institutes of Health Stroke Scale score was 7 (interquartile range: 5–12). A total of 72.1% (186/258) patients were treated with intravenous alteplase and in 41.8% (84/201), recanalization of the occlusion (revised arterial occlusive lesion score 2b/3) was seen on follow-up computed tomography angiography. Excellent functional outcome was achieved by 50.0% (129/258), and 67.4% (174/258) patients gained functional independence, while 8.9% (23/258) patients died within 90 days. Recanalization was observed in 21.4% (9/42) patients who were not treated with alteplase and 47.2% (75/159) patients treated with alteplase ( P =0.003). Early recanalization (adjusted odds ratio, 2.29 [95% CI, 1.23–4.28]) was significantly associated with excellent functional outcome, while intravenous alteplase was not (adjusted odds ratio, 1.70 [95% CI, 0.88–3.25]). Conclusions: One of every 2 patients with MeVO did not achieve excellent clinical outcome at 90 days with best medical management. Early recanalization was strongly associated with excellent outcome but occurred in <50% of patients despite intravenous alteplase treatment. Abstract : Supplemental Digital Content is available in the text.